Registration of three Arkot 0908 cotton germplasm lines. Issue 3 (2nd August 2021) - Bourland, Fred M.; Chee, Peng; Jones, Don C.
Abstract: Arkot 0908‐52 (Reg. no. GP‐1091, PI 697035), Arkot 0908‐56 (Reg. no. GP‐1090, PI 697034), and Arkot 0908‐60 (Reg. no. GP‐1089, PI 697033) are conventional cotton ( Gossypium hirsutum L.) germplasm lines released by the Arkansas Agricultural Experiment Station in October 2020. The lines are high performing, early maturing germplasm derived from parents ('GA 230' and 'UA222') having contrasting backgrounds and maturity. The lines produced higher lint yields than UA222 and 'UA48' over 5 yr and at four test sites in Arkansas, producing similar relative lint yields across all test sites and about 15 and 25% higher than lint yields of UA222 and UA48, respectively. Additionally, they had smaller seed while producing more seed per area and more or equal amount of lint per seed than UA222 or UA48. Arkot 0908‐52 and Arkot 0908‐60 performed well in the 2017 Regional High Quality Test and the 2017 Regional Breeders Network Test, respectively. Leaf pubescence and bract trichome density of Arkot 0908‐56 were greater than Arkot 0908‐52, Arkot 0908‐60, and UA48. Stem pubescence density of Arkot 0908‐52 and Arkot 0908‐56 was similar to UA48 and UA222 but greater than Arkot 0908‐60. All three lines displayed high resistance to bacterial blight and were similar to UA222 and UA48 in their response to other diseases. Arkot 0908‐56 and Arkot 0908‐60 were more resistant to tarnished plant bug than Arkot 0908‐52 and UA48, but all were more susceptible to tarnished plant bug than UA222. Fiber quality of Arkot 0908‐52 and Arkot 0908‐56 was similar to UA48, while fiber quality of Arkot 0908‐60 was similar to UA222. Core Ideas: Three Arkot 0908 lines were derived from crossing UA222 with GA 230. The three Arkot 0908 lines produced higher yields than UA222 or UA48. Fiber quality of the three lines was equal to or better than UA222. GA 230 parent contributes diversity to UA cotton germplasm.